Homocysteine restrains hippocampal neurogenesis in focal ischemic rat brain by inhibiting DNA methylation. (July 2021) - Gou, Yun; Ye, Qi; Liang, Xiaoshan; Zhang, Qiang; Luo, Suhui; Liu, Huan; Wang, Xuan; Sai, Na; Zhang, Xumei
Abstract: Ischemic stroke represents a major cause of mortality worldwide. An elevated level of homocysteine (Hcy) is recognized as a powerful risk factor of ischemic stroke. We previously reported that Hcy induces cytotoxicity and proliferation inhibition in neural stem cells (NSCs) derived from the neonatal rat hippocampus in vitro . However, the toxic potential of Hcy on NSCs and its underlying mechanisms are not entirely clear in ischemic brain. Since DNA methylation is critical for establishing the diverse cell fates in the central nervous system, we hypothesized that negative effect of Hcy (an intermediate in the one-carbon metabolism) on neurogenesis might be link to DNA methylation in ischemic stroke. In our study, the rats in Hcy intervention group were intraperitoneally injected with 2% Hcy solution (5 mL/kg/d) for 7 consecutive days before MCAO surgery until they were sacrificed. Our study indicated that Hcy inhibited NSCs self-renewal capacity, which was exhibited by lowering the number of DCX + /BrdU + and NeuN + /BrdU + in ischemic brain hippocampus. A reduction in the activity of the DNA methyltransferases (DNMTs), total methylation level and the number of 5mC + /NeuN + and DCX + /5mC + cells was observed in Hcy-treated ischemic brains. Additionally, Hcy also induced an increase in S-adenosylhomocysteine (SAH), and a decrease in the ratio of S-adenosylmethionine (SAM) to SAH. These results suggest that the alterations in DNA methylation may be an important mechanism by which Hcy inhibits neurogenesis after stroke. Hcy-induced DNA hypomethylation may be mainly caused by a reduction in the DNMT activity which is regulated by the concentrations of SAM and SAH. Maintaining normal DNA methylation by lowering Hcy level may possess therapeutic potential for promoting neurological recovery and reconstruction after stroke. Highlights: Homocysteine inhibits the proliferation and differentiation of hippocampal neural stem cells in ischemic brain. Homocysteine resulted in DNA hypomethylation and ultimately inhibited the neurogenesis in ischemic brain. Homocysteine-induced DNA hypomethylation may be caused by a reduction in the DNA methyltransferases activity.